Fostering Empathy and Social-Emotional Learning in Students with Learning Disabilities through HCI and Augmented Reality - Ghazy Almakky, Hana (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This systematic review synthesizes the suggested approach to designing human-computer interaction (HCI) in conjunction with augmented reality (AR) applications to enhance learner empathy with learning disabilities (LDs). However, as the popularity of both AR and HCI increases within the context of education, there is a dearth of literature on integrating the two in supporting social and emotional learning (SEL) in students with LDs. SEL refers to the learning process by which a person gains academic and social competencies and can also apply, cipher, and internalize the competencies related to emotional, social, and academic aspects of human life. This review summarizes the studies published between 2015 and 2024. It discusses how the AR-based immersive and interactive learning contexts can improve these students’ social and emotional learning and reduce their technophobia. It is evident from the highlighted gaps that comprehensive features, user-centered design (UCD) principles, and gradual implementation of technology are possible solutions to enhance the learning and emotional development of students with LDs. This paper highlights the existing gaps in literature and provides recommendations for future and practical research.